Evaluation of the current clinical and bacteriological profile in the tubotympanic type and the atticoantral type chronic suppurative otitis media - Anton Budhi Darmawan; Bella Jovita Darmayan; Vitasari Indriani (Published by Universitas Gadjah Mada, 2026)
Chronic suppurative otitis media (CSOM) is a leading cause of preventable hearing loss in low- and middle-income countries, including Indonesia. It is classified into tubotympanic and atticoantral types, yet local comparative data regarding clinical features and bacteriological profiles remain limited. This study aimed to evaluate and compare the clinical manifestations, microbiological patterns, and antibiotic susceptibility profiles of both CSOM types in a tertiary hospital. A cross-sectional study was conducted from November 2021 to August 2022 involving patients aged ≥17 yr with active CSOM. Data were collected through interviews, otoendoscopy, and pure-tone audiometry. Ear swabs were cultured and antibiotic susceptibility testing was performed. Ear-based analysis was applied for clinical and audiological variables (73 ears from 66 patients), and isolate-based analysis for microbiology. Exploratory comparisons between CSOM types were performed using Chi-square or Fisher’s exact tests. Among 73 ears, 50 (68.5%) were tubotympanic and 23 (31.5%) atticoantral. Hearing loss was present in 98.6% of ears, most commonly mixed (47.9%) and conductive (42.5%), with predominantly moderate to severe degrees. Facial nerve palsy occurred in one atticoantral case (1.4%). No significant differences in clinical or audiological profiles were observed between types (p > 0.05). Of 76 bacterial isolates obtained from 69 culture-positive samples, Gram-negative organisms predominated (81.6%). Pseudomonas aeruginosa was the most frequent pathogen (57.9%), followed by Proteus mirabilis (13.1%). Pseudomonas aeruginosa showed highest susceptibility to amikacin, meropenem, and piperacillin–tazobactam, with reduced susceptibility to fluoroquinolones and cephalosporins. Gram-positive bacteria were most susceptible to linezolid, tigecycline, tetracycline, and quinupristin/dalfopristin. In conclusion, tubotympanic CSOM remains the predominant subtype, with P. aeruginosa as the principal pathogen. Moderate-to-severe hearing loss is common in both disease types. Clinical symptoms alone cannot differentiate CSOM subtypes, underscoring the importance of otoscopic or otoendoscopic examination and culture-guided therapy to optimize management and minimize antimicrobial resistance.